Pemikiran KH. A. Wahid Hasyim (Religius -Rasional) Tentang Pendidikan Islam dan Relevansinya dengan Pendidikan Islam Kontemporer - Nursaima Putri Siregar; Maragustam Siregar (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Among the many thinkers and observers of Islamic education, Wahid Hasyim's name is still rare and has received less attention about his ideas regarding the problems of contemporary Islamic education. In addition to his thoughts and struggles related to the State, the figure of Wahid Hasyim also thinks a lot about the strategy and progress of Islamic education in facing various challenges and demands of the community on the needs of the world of education. Islamic education has always been an interesting study not only because it has its own characteristics, but also because it is rich in concepts that are no less quality than modern education. Many figures have made innovations in the world of education, one of which is Wahid Hasyim's thought in advancing Islamic education. This research uses the literature method (liberary reseach) The results of this study are the educational concepts of K.H. Abdul Wahid Hasyim, namely, 1) Religion, 2) Development of students' potential, 3) Social, and 4) National spirit. Those are the 4 pillars of the concept of Islamic education contributed by K.H. Abdul Wahid Hasyim in the Islamic education system.